Sensory profile and chemical quality of Merlot aged in barrels of different wood species - PEREIRA, Amanda de Andrade Marcondes; ACEVEDO, Maria Soledad Moura Soares Fernández; VARGAS, Michel Rudan Isaias; ALCARDE, André Ricardo (Food Science and Technology, 2024)
The cultivation of Vitis vinifera varieties in Brazil was established in 1970. With the opening of the market to imported labels and a greater variety of wines, viticulture became more competitive, and consumers became more demanding. The aging of wine is a system that involves several reactions based on the extraction of molecules from the wood and also on the micro-oxygenation of beverages. The objective of this study was to investigate the sensorial and chemical evolution of wines aged in barrels of different woods: French oak (Quercus petraea), Amburana (Amburana cearensis), and Jequitibá Rosa (Cariniana legalis). The comparison of the sensorial and chemical characteristics of the aged wine with the non-aged one allowed us to know the modifications resulting from the maturation time. Their distinct evolution among the different species was identified through chromatographic analysis of maturation congeners. Perceived sensory characteristics and acceptance of Brazilian woods were measured using the Napping and UltraFlash Profile methodologies. Tropical woods stood out in terms of acceptance by tasters, and the sensory attributes listed by the panel differ between both.